Prevention of lumbar injuries in diving - Kaneoka, K. (FINA World Sports Medicine Congress, 18, 2016)
Dr. Koji Kaneoka (JPN) talks about "Prevention of Lumbar Injuries in Diving" at the FINA World Sports Medicine Congress 2016 (15:52 min).